Relaciones que establecen los fotógrafos con los familiares, espacios, objetos y tiempos afectados por la desaparición forzada (2018)
This work is part of the investigation Ante el dolor de los demás: repertorios institucionales y prácticas intersubjetivas en el trabajo con víctimas del conflicto armado colombiano, led by the profesor Juan Pablo Aranguren Romero, specifically in forced disappearance. This is a phenomenon that has several edges from which it can be addressed, however, in this specific case, we speak of its photographic representation. However, the central focus of this research is to investigate the type of relationships that the photographer establishes with what he photographs. This approach has not been sufficiently developed, and has more information on this topic is known in greater depth of images related to enforced disappearance. Interviews were conducted with six photographers who represents the consequences of enforced disappearance at different levels. The photographers were chosen following the criterion of excellence in their work. Subsequently the interviews were classified into three independent categories and two cross-linked categories...